Optimalisasi Pendampingan Proses Sertifikasi Halal UMK oleh PPH di Banyuwangi - Alfiyah, Nurul; Kareja, Novilia; Indraloka, Aldy Bahaduri (Program Studi Ekonomi Syariah IAIN Parepare, 2024)
The halal certification obligation for MSMEs will be implemented in October 2024, so that the acceleration of halal certification must be carried out by BPJBH (Halal Product Guarantee Organizing Agency) starting for food products, beverages, slaughtered products and slaughtering services, raw materials, food additives and auxiliary materials for food and beverage products. Banyuwangi has quite a lot of MSMEs, according to data from the East Java Cooperatives and MSMEs Service (2023) the number of MSMEs in Banyuwangi is 38,688 MSMEs. The Banyuwangi government also provides support for the potential of MSMEs in Banyuwangi. The aim of this research is to analyze the optimization carried out by the Halal Product Process Assistant (PPH) in order to assist or assist the halal certification process for MSMEs in Banyuwangi. The research method used is a qualitative approach, with an interactive model analysis method, using primary and secondary data sourced from observation, interviews and literature review. The results of this research show that the BPJBH Halal Product Process Facilitator (PPH) in Banyuwangi has provided assistance to MSMEs in terms of applying for halal certificates, but several obstacles are still found in it. With this effort, it is hoped that the obstacles faced can be resolved so that assistance to MSMEs in applying for halal certification in Banyuwangi will be more optimal.